Rent-a-girlfriend. Volume 2 - Miyajima, Reiji (Kodansha Comics, 2020)
"In today's Japan, rental services can deliver an afternoon with a friend, a parent, even a fake girlfriend! After a staggering betrayal by his college girlfriend, Kazuya gets just desperate enough to give it a try. But he quickly discovers how complicated it can be to rent an emotional connection ... and his new girlfriend, who's trying to keep her side hustle secret, will panic when she finds out her real life and Kazuya's are intertwined in surprising ways! It's sweet but naive boy meets cute but ruthless girl in this 21st-century manga rom-com! ... As Kazuya and his rental girlfriend's lives become more and more intertwined, their feelings become as complicated as ever. After awkward encounters with their family and friends, who now think they're really dating, and a heated exchange with Kazuya's ex, the best thing to keep their relationship professional might be taking some time apart--but fate may have other plans ..."--Provided by publisher